KAJIAN AGROINDUSTRI UNGGULAN WILAYAH PESISIR KOTA BENGKULU - Bonodikun Bonodikun; Putri Suci Asriani; Ellys Yuliarti (Jurnal Agrisep)
Plan-based agro-industry development of coastal areas in the city of Bengkulu continue in effect and be a leading program in a variety of program design opportunities. However, up to now there has been a lot of information that can be presented relating to the advantages of each agro-industry that has growing to be driven by the strength of coastal resources are available as ongoing. Availability of coastal resources be a key determinant of the agro-industry excellence being developed. The wide variety of resources will determine variations agroindustrial commodities. This study will identify leading agro-industry coastal areas with potential priority approach coastal resources and the efficiency of application of processing technology has been used. The study was conducted from May to November 2014, applying analytical methods Location Quotion (LQ) and Shift Share (SS). The results obtained from this study is the leading commodity in Bengkulu city coastal resources better competitiveness is the fisheries product and milkfish. The potential commodity of coastal resources Bengkulu city which also has a good competitiveness is catfish. For the development of agro-industries in the coastal areas of the Bengkulu city is directed at the use of resources that have both advantages and competitiveness, which is based on the fisheries product resources and milkfish. Catfish agro-industries are also recommended to be developed for this commodity has potential advantages and has good competitive.